Approximate arithmetic coding for bus transition reduction in low power designs. - Lekatsas, H. (IEEE Transactions on VLSI systems)
We present a method for reducing the power consumption of compressed-code systems by selectively inverting bits that are transmitted on the bus. By incorporating bus inversion into code compression/decompression, we reduce power consumption with no cost in hardware or power relative to code compression without inversion. Inverting has to be done carefully to ensure that the codes can still be decoded. As an additional challenge, compression will generally increase bit-toggling as it removes redundancies from the code transmitted. Therefore, we need to find the right balance between compression ratio and bit-toggling reduction. This paper presents a suitable algorithm that will combine approximate compression techniques with bit-toggling reduction and will explore the various tradeoffs. We take advantage of the approximations introduced to modify codes and reduce bit-toggling, while maintaining compression performance and decoding speed. An interesting result that is derived from our work is that high compression ratios do not necessarily result in the lowest power consumption. By using our method, bus-related power consumption has been reduced by as much as 35% compared to a system with no compression, and as much as 14% compared to a compressed-code system. Bit-toggling reduction does not impose any additional hardware costs other than the decompression engine. We also present a detailed analysis on how bus widths affect bit-toggling when transmitting compressed code, and we show experimental results on ARM, MIPS, and SPARC code. We finally compare our work with Bus Invert and show results that are superior except for the random data case where Bus Invert performs better.